Computer Safety, Reliability, and Security 30th International Conference, SAFECOMP 2011, Naples, Italy, September 19-22, 2011, Proceedings - Flammini, Francesco; Bologna, Sandro; Vittorini, Valeria (Programming and Software Engineering,, 2011)
This book constitutes the refereed proceedings of the 30th International Conference on Computer Safety, Reliability, and Security, SAFECOMP 2011, held in Naples, Italy, in September 2011. The 34 full papers presented together were carefully reviewed and selected from 100 submissions. The papers are organized in topical sections on RAM evaluation, complex systems dependability, formal verification, risk and hazard analysis, cybersecurity and optimization methods.